Importance of peripheral blood smears study in the elderly - Nelson Rafael Terry Leonard; Carlos Alberto Mendoza Hernández (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2017)
The study of smear of peripheral blood consists on specifying and informing the morphological alterations of blood elements; This is a simple, inexpensive, quick exam in reporting its results, but at the same time requires much care and experience, given the time and interest that is devoted to its learning, the quality of the extension and its staining. We present a literature review describing the variations of the peripheral lamina that can occur in diseases that most frequently affect the elderly, with the objective of offering a material for teaching residents of Hematology and Geriatrics.